Mekanisme Pengendalian Penyakit Busuk Batang Jeruk oleh Khamir, Kitosan, Cendawan Mikoriza Arbuskular, dan Bakteri Simbiotiknya - Khairani, Hagia Sophia; Sinaga, Meity Suradji; Mutaqin, Kikin Hamzah (Jurnal Fitopatologi Indonesia, 2017)
Plant diseases become an important constraint on citrus production.  Stem rot disease caused by Botryodiplodia theobromae is a major disease on citrus in Indonesia. This study was aimed to evaluate the mechanism of yeast, arbuscular mychorrhiza fungi (AMF), symbiotic bacteria of AMF and chitosan in controlling stem rot disease.  In vitro study was performed to evaluate the mechanism of antibiosis, hyperparasitism, production of volatile compounds, and production of chitinase enzyme. The experiment was continued by in planta assays using yeast, AMF, symbiotic bacteria of AMF, and chitosan either singly or in combination. The experiments were performed using completely randomized design with 3 replications. Disease progress were observed based on its latent period, AUDPC, infection rate, AMF association rate, and total phenol content. In vitro studies indicated that the yeasts showed hyperparasitism to B. theobromae with affinity of 26 cells per hyphae, produced volatile compounds with relative resistance level (RRL) 29.1%, and produced chitinase. Selected symbiotic bacteria from AMF showed antibiosis with RRL 42.9%, production of volatile compounds with RRL 26.7%, and has 98% homology with Bacillus subtilis from Vietnam. Application of yeast + AMF + chitosan delayed disease latent period and suppressed disease incidence. Single AMF and combination of yeast + AMF suppressed disease severity, infection rate, and AUDPC. Application of yeast + AMF showed highest association level of AMF and total phenol content. Therefore, the application of AMF and yeast + AMF is recommended in controlling citrus stem rot disease.